2018
DOI: 10.1080/15384047.2018.1433501
|View full text |Cite
|
Sign up to set email alerts
|

A prognosis and impact factor analysis of DC-CIK cell therapy for patients with hepatocellular carcinoma undergoing postoperative TACE

Abstract: Dendritic cell-cytokine-induced killer (DC-CIK) cell therapy has been experimentally implemented for enhancing anti-tumoral immunity in patients with hepatocellular carcinoma (HCC) undergoing postoperative transcatheter arterial chemoembolization (POTACE). We performed a retrospective study to evaluate the clinical efficacies of DC-CIK cell therapy and its correlations with several immune factors of the primary tumors. The overall survival time of HCC patients with HBV infection in the study group (POTACE plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Eighteen studies determined the mPD-L1 expression in tumor tissues. Among them, 16 studies analyzed the relationship between mPD-L1 expression and OS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], seven studies analyzed the relationship between mPD-L1 expression and DFS [14,21,23,25,26,30,31], and six studies analyzed the relationship between mPD-L1 expression and RFS [15,19,20,22,27,28]. Besides, only three studies were conducted in Western countries [20,24,31].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies determined the mPD-L1 expression in tumor tissues. Among them, 16 studies analyzed the relationship between mPD-L1 expression and OS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], seven studies analyzed the relationship between mPD-L1 expression and DFS [14,21,23,25,26,30,31], and six studies analyzed the relationship between mPD-L1 expression and RFS [15,19,20,22,27,28]. Besides, only three studies were conducted in Western countries [20,24,31].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Besides, only three studies were conducted in Western countries [20,24,31]. The remaining 16 studies were conducted in Asia, of which 12 studies were from China [14,[16][17][18][19]21,22,[25][26][27][28][29]. In particular, Dai et al [26] analyzed data from two independent groups, and both of them were included in this meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death in men worldwide, and it is generally considered resistant to chemotherapy. 1 HCC is often diagnosed at advanced stage due to its insidious onset and nonspecific nature of the symptoms. 2 For patients with advanced and unresectable HCC, transarterial chemoembolization (TACE) and tyrosine kinase inhibitors are considered as standard therapeutic methods.…”
Section: Introductionmentioning
confidence: 99%
“…3 As a widely accepted treatment strategy for HCC, TACE could effectively inhibit tumor progression. 1,4 However, TACE has been shown to induce hypoxia and elevate the level of proangiogenic factor vascular endothelial growth factor (VEGF) in the residual surviving HCC tissues, resulting in significant neoangiogenetic reactions and relapses after treatment. [5][6][7] Since there is no ideal treatment for HCC patients who experienced disease progression following TACE, it is of vital importance to develop novel therapeutic methods for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The application of CIK cells as an adoptive immunotherapy is important for the treatment of cancer, since several clinical studies have confirmed the safety of CIK therapy for patients [17,18]. Numerous clinical studies have been recently performed, whereby adjuvant infusions of CIK cells following surgical resection or chemotherapy demonstrated a significant increase in survival time [19,20]. The first clinical study included 10 patients with metastatic renal carcinoma, colorectal cancer and lymphoma.…”
Section: Introductionmentioning
confidence: 99%